KEMAMPUAN PENALARAN MATEMATIS SISWA DALAM MENYELESAIKAN PERMASALAHAN HOTS PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Zikriatul Fitriah; Redo Martila Ruli (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Mathematical reasoning ability refers to a person's ability to make conclusions and generate new assertions in order to solve mathematical problems. The capability to reason mathematically encourages students to think logically, considering it a crucial part of the learning process. The aim of this study was to analyze at students' mathematical reasoning ability when solving HOTS problems with material for the Three Variable Linear Equation System (SPLTV). This research applies descriptive research with a qualitative approach. The subjects in this research were 15 students from a high school in Karawang Regency in grade X science The researcher give five written test questions based on Higher Order Thinking Skills and conducted interviews on selected subjects to obtain data. Based on the results of the study, obtained 4 students belonging to the high category, 7 students belonging to the moderate category, and 4 students belonging to the low category. The conclusion of this research is the students' mathematical reasoning ability in solving HOTS problems on the material of a system of linear equations of three variables is classified as moderate.